Proceso administrativo-operativo y su incidencia en el rendimiento económico de la ferretería ferreDomínguez de la ciudad de Quevedo, año 2023 - Cevallos Domínguez, Santiago Andrés (2025)
The purpose of this research is to evaluate the administrative and operational processes and their impact on the economic performance of FerreDomínguez Hardware Store, located in the city of Quevedo, Los Ríos province. The objective is to identify the main weaknesses in internal management and propose solutions that will optimize resources and improve the business's profitability. A mixed approach using quantitative and qualitative techniques was used. Data collection included semi-structured interviews with the manager, administrator, and president of the hardware store, as well as surveys of operational and customer service staff. These tools provided insight into employee perceptions of the organizational structure, administrative processes, and assigned functions. The results revealed the absence of an efficient administrative and operational system, a lack of strategic direction, and a job manual. Furthermore, it was found that staff are completely unaware of their specific responsibilities, which limits performance and directly impacts business profitability. The findings show that deficiencies in administrative and operational management negatively impact the hardware store's efficiency and profitability. Therefore, an improvement proposal was designed that includes the development of a job manual with clear responsibilities, performance indicators, and internal communication guidelines. This tool is intended as a strategic guide to improve decision-making, strengthen internal organization, and contribute to the company's sustained economic development.